Tailored elastic surface to body wave Umklapp conversion - Gregory J. Chaplain (Nature Portfolio, 2020)
Umklapp scattering, an effect that has been conventionally studied in phonon systems in quantum transport, is studied here in an elastic system. The authors demonstrate mode conversion from surface Rayleigh waves into bulk waves that have uniquely tunable properties.